2020
DOI: 10.3390/en13184700
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling and Experimental Validation of Twin-Screw Expanders

Abstract: Positive displacement machines have been identified as appropriate expanders for small-scale power generation systems such as Organic Rankine Cycles (ORCs). Screw expanders can operate with good efficiency in working fluids under both dry and two-phase conditions. Detailed understanding of the fluid expansion process is required to optimise the machine design and operation for specific applications, and accurate design tools are therefore essential. Using experimental data for air expansion, both CFD and chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…to name a few. In the realm of twin screw machines, single and multi-phase screw expanders have been modeled and validated with GT-SUITE [6,7]. However, to the authors' knowledge, this is the first study modeling the thermodynamics in a twin screw pump with the GT-SUITE solver.…”
Section: D Thermodynamic Chamber Modelmentioning
confidence: 99%
“…to name a few. In the realm of twin screw machines, single and multi-phase screw expanders have been modeled and validated with GT-SUITE [6,7]. However, to the authors' knowledge, this is the first study modeling the thermodynamics in a twin screw pump with the GT-SUITE solver.…”
Section: D Thermodynamic Chamber Modelmentioning
confidence: 99%
“…Positive displacement expanders have thus gained popularity recently for small-scale power generation and waste heat recovery applications based on ORC. Experimental investigations of ORC-based power plants using positive displacement expanders of various types such as scroll [15][16][17][18][19], rotary vane [20,21], swash-plate [22], and screw [23][24][25] have been realized of late. As the primary component of the thermal-to-power conversion process of the ORC, the expander plays a vital role in the overall performance of the ORC [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The investigations of Stosic 2 and Pascu et al 12 have shown that the use of new techniques for rotors profiling helped to manufacture rotors of complex shapes with tolerances of the order of few microns, which improved efficiencies. Also, a limited number of the previous investigations have been carried out 19,20 to characterise flow leakages using experiments and CFD simulations. The gas pulsations are also a main source of noise within the discharge cavity and have been investigated since 1986 by many authors.…”
Section: Introductionmentioning
confidence: 99%